Population-based screening leads to improved glaucoma diagnosis in Kazakhstan - Lyaylya Bolatovna Tashtitova; Neilya Akhmetovna Aldasheva; Ardak M. Auyezova; Mukhit Kulmaganbetov (Taylor & Francis Group, 2023)
AbstractTo analyse the effect of the state screening program for glaucoma, funded by the Kazakhstan State programs for the health care system "Salamatty Kazakhstan" (2011-2015) and "Densaulyk" (2016-2019), on glaucoma diagnosis. This study involved 1,620,658 men and women 40-70 years of age. State screening for glaucoma includes measures of intraocular pressure (IOP) and corneal thickness. Data for glaucoma incidence were retrieved from the state statistics dataset. Studies of vulnerable age groups and ophthalmologists' availabilities were assessed, and correlations with glaucoma detection were determined. For the statistical analysis, MATLAB application package version R2017b (MathWorks, USA) was used. The number of registered glaucoma patients was 43,337 in 2010. In 2016, following the screening program, this figure increased to 68,195. A 49% increase in newly identified glaucoma cases from 70.8 (in 2010) to 124 (in 2016) per 100,000 population was determined. Thus, the sufficiency and effectiveness of the screening program were confirmed by the increase in the number of patients diagnosed with glaucoma, which also depended on age. A correlation between suspected glaucoma and age groups was exposed with the observation of a high number of cases in the older population. The state screening programs for glaucoma in the Republic of Kazakhstan constitute initial steps in the prevention of irreversible blindness and disability due to glaucoma. Such screening seems to allow timely and adequate diagnosis of the disease in people>40 years of age.